Upaya Pendidikan Kesehatan Untuk Meningkatkan Pengetahuan Tentang Gout Arthritis Pada Ny.Y - Ihsan Fauzi, Muhammad Ihsan; , Supratman, M.Kep, Ph.D (2017)
Introduction: Gouty arthritis (gout) is a compound which is difficult to dissolve in water or can be called bythegarbage of normal metabolism that results from the digestion of oteins that should be excreted through the kidneys, sweat or feces. Methods: case study approach is descriptive method to collect data, analyze the data and draw conclusions. How to use such interviews, observation, and physical examination and medical progress notes. Results: After being given the nursing actions 3x 60-minute meetings, family and patient understanding of disease gout arthritis (gout). Discussion: After being awarded a nursing actions 3x 60-minute meeting, expected family is able to know the basic knowledge of uric acid and were able to reduce the pain by giving health ation and deep breathing relaxation techniques. Conclusion: Health education is given proven to increase the knowledge overcome the pain and taught relaxation techniques can reduce pain due to gouty arthritis (gout).